Regeneration of plantlets from leaf derived Callus of ammi majus-a medicinal plant - SANJEEV KUMAR (International Journal of Pharma and Bio Sciences, 2017)
An efficient protocol was developed for high frequency plant regeneration from leaf explants of Ammi majus. Ammi majus L. (Apiaceae) is a herb of pharmaceutical as well as ornamental interest and used in the treatment of leucoderma. Since in Ammi majus the seed set and germination is poor attempts were made to propagate the plants through tissue culture. The callus from cotyledonary leaves obtained on Murashige and Skoog’s (MS) medium supplemented with a-indoleacetic acid (IAA) + Kinetin (Kn) + Casein hydrolysate (CH), differentiated shoots in 100% cultures when adenine and glutamine were added to the above medium. Plantlets resulted on MS medium with indolebutyric acid (IBA) and glutamine.